Attenuation of antigenic immunogenicity by kynurenine, a novel suppressive adjuvant - Duan, Zhiqing (Hum Vaccin Immunother, 2014)
A novel therapeutic strategy is required for autoimmune diseases characterized by the production of autoantibody, because current clinical strategies have limitations. Vaccination against autoimmune diseases is a feasible strategy because vaccines induce immune response memory and the antigen specificity. However, no suitable adjuvant is available to direct the immune response toward tolerance or suppression. In the current study, we evaluated whether kynurenine (Kyn) could serve as a novel suppressive adjuvant to decrease the humoral immune responses against hepatitis A virus (HAV) in the ICR mouse model in vivo and lipopolysaccharide (LPS) in B cells in vitro. The underlying mechanisms of Kyn-mediated suppression of LPS-induced IgM responses were explored. The results showed that Kyn significantly decreased HAV immunogenicity when co-administered with HAV, and that Kyn (100 μM/1000 μM) impaired IgM generation compared with that induced by LPS alone. We also demonstrated that microRNA30b (miR30b) played a critical role in the process of Kyn-mediated suppression of IgM responses induced by LPS, and that Bach2, a transcriptional repressor of B cell terminal differentiation, was a novel target of miR30b. These findings suggest that Kyn can serve as a novel and effective suppressive adjuvant for vaccines.